PENGARUH LOAN TO DEPOSIT RATIO DAN BEBAN OPERATIONAL PER PENDAPATAN OPERASIONAL TERHADAP RETURN ON ASSET PADA PT. BANK MEGA Tbk YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) - Krida Puji Rahayu; Rudi Sanjaya (RJABM (Research Journal of Accounting and Business Management), 2021)
The purpose of this study was to determine the effect of Loan to Deposit Ratio (LDR) and Operating Expenses per Operating Income (BOPO) on Return On Assets (ROA) at PT. Bank Mega Tbk in 2010-2019. This study uses secondary data obtained through documentation in the form of annual financial reports from PT. Bank Mega Tbk, officially accessed from www.bankmega.com Data analysis was carried out using Descriptive Analysis, Classical Assumption Test consisting of Normality Test; Non-Multicollinearity Test; Non Heteroscedasticity Test; and Non-Autocorrelation Test, Model Feasibility Test consisting of Multiple Correlation Test (R); Determination Correlation Test (R Square); and the F Test (Anova), as well as the Effect of Causality Test consisting of the Simple Linear Regression Coefficient; Multiple Linear Analysis; and Hypothesis Testing (T Test).The results of the study found that the Loan to Deposit Ratio on Return On Assets at PT Bank Mega in 2010-2019 with a significant value of 0.826 where 0.826 > 0.05 means that the Loan to Deposit Ratio has no effect on Return On Assets. Operating Expenses per Operating Income on Return On Assets at PT Bank Mega in 2010-2019 with a significant value of 0.000 where 0.000 < 0.05 means that Operational Expenses per Operating Income have an effect on Return On Assets. And Loan to Deposit Ratio and Operating Expenses per Operating Income on Return On Assets at PT Bank Mega in 2010-2019 with a significant value of 0.010 where 0.010 < 0.05 means that Loan to Deposit Ratio of Operating Expenses per Operating Income has a joint effect on Return On Assets.